PENGARUH PENYULUHAN CUCI TANGAN TERHADAP PENGETAHUAN ANAK TUNAGRAHITA DI SDLB NEGERI TUBAN - Novia Dwi Astuti (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
Students are expected to get knowledge about clean and healthy lifestyle or in Indonesian is called Perilaku Hidup Bersih dan Sehat (PHBS). In fact, the program that is set by the government in PHBS application isn't optimally executed. The first survey data shows that the mental-disabled student's knowledge about PHBS (hand-washing) is less. The purpose of this research is for knowing the influence of hand-washing Education towards PHBS knowledge to mental-disabled students. Methods: The population of this research is 30 mental-disabled students from state mental-disabled elementary school of Tuban or SDLB Negeri Tuban with hand-washing learning SOP and questionnaire paper for knowledge scoring. The independent variable is clean hand-washing training and the dependent variable is PHBS knowledge to mental-disabled student  that scored by structural interview with pre-test and post-test. Results: As the result, it shows the most respondents have enough knowledge before the treatment, that is 18 (60,0%) students and almost all respondents have good knowledge after the treatment, that is 28 (93,3%) student. Conclusion: From this research result, the school is expected to apply the clean hand-washing training to develop PHBS knowledge learning in school periodically.